The frequency, characteristics and aetiology of stroke mimic presentations: a narrative review. (February 2019) - McClelland, Graham; Rodgers, Helen; Flynn, Darren; Price, Christopher I.
Abstract : A significant proportion of patients with acute stroke symptoms have an alternative 'mimic' diagnosis. A narrative review was carried out to explore the frequency, characteristics and aetiology of stroke mimics. Prehospital and thrombolysis-treated patients were described separately. Overall, 9972 studies were identified from the initial search and 79 studies were included with a median stroke mimic rate of 19% (range: 1–64%). The prehospital median was 27% (range: 4–43%) and the thrombolysis median 10% (range: 1–25%). Seizures, migraines and psychiatric disorders are the most frequently reported causes of stroke mimics. Several characteristics are consistently associated with stroke mimics; however, they do not fully exclude the possibility of stroke. Nineteen per cent of suspected stroke patients had a mimic condition. Stroke mimics were more common with younger age and female sex. The range of mimic diagnoses, a lack of clear differentiating characteristics and the short treatment window for ischaemic stroke create challenges for early identification. Abstract : Supplemental Digital Content is available in the text.